URGENSI IMPLEMENTASI JURNALISME PATRIOTIK DALAM EKOSISTEM KEWARTAWANAN INDONESIA: TINJAUAN HISTORIS JURNALISME KEMERDEKAAN - Nurdin, Iman; Abidin, Muhammad Salman; Solihin; Maulana, Muhammad Yunus (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2024)
Abstract:The existence of Indonesia as an independent nation is intricately linked to the vital role of journalism worldwide. However, Indonesian journalism currently faces serious challenges, triggering polarization and societal divisions. To address these issues, a new paradigm of patriotic journalism emerges as a proposed solution. This research critically aims to understand the concept of patriotic journalism, focusing on the Indonesian journalistic context. Critical review methodology is employed to provide initial insights into the patriotic journalism paradigm. Findings indicate that patriotic journalism encounters challenges in objectivity, identity conflicts, reporting perspectives, and consistency in goals and practices. Nonetheless, the study offers solutions such as justice implementation, transparency, adapting to core values, engaging in new media interactions, global journalism ethics, and aligning goals with more suitable practices. Although the goals of patriotic journalism align with Indonesia's journalism ecosystem, its advocated practices aren't always congruent. This paper proposes alternative ideas to enhance alignment between patriotic journalism and Indonesia's journalistic ecosystem. In conclusion, implementing patriotic journalism holds significant potential in addressing national issues, particularly concerning societal unity. Suggestions for future research include delving deeper into reporting deemed patriotic using methodologies like content analysis or phenomenology. Keyword: Journalistic Genre, Patriotic Journalism, Indonesia’s Journalistic Ecosystem, Critical Review